Analisis Perencanaan dan Rekrutmen Guru pada Dinas Pendidikan Kabupaten Lombok Tengah - Roni Pujiantari; Dwi Wahyudiati (PALAPA, 2022)
This study uses a naturalistic qualitative approach to describe the management of human resources for educators at the Education Office of Central Lombok Regency in a complete, natural and in-depth manner. The Education Office of Central Lombok Regency in planning and recruiting educators by evaluating and analyzing the needs of teacher shortages in each school based on the teacher needs proposed by the school principals. Then coordinate in the form of meetings, meetings and joint deliberation in order to propose planning for educators proposed by the school. Planning for the needs of educators (teachers) at the Education Office of Central Lombok Regency, includes two things: (1) the planning process for teacher needs aims to ensure the fulfillment of needs in organizational units, planning is carried out by analyzing internal and external factors, such as resource and teacher needs . After the planning is done, it is known that the required manpower with a certain level of ability or skill is known; (2) analysis of teacher needs. The planning starts from the analysis of currently available teacher resources. The analysis includes two things, namely; job descriptions and job specifications. A job description describes the tasks or work performed, while a job specification includes the skills and abilities needed to carry out the task. In terms of recruitment of educators, the Education Office of Central Lombok Regency is based on the needs of educators by using academic, administrative, health and qualification selections that have been determined, in its implementation it still depends on the provisions of the Education and Training Personnel Agency (BKPP) of Central Lombok Regency. its nature is only to plan human resources and propose employees who have been previously planned, while the recruitment process is carried out by the regional personnel agency. Thus the Education Office of Central Lombok Regency as one of the organizations or institutions implementing regional autonomy authority in the field of education, has a very strategic function in managing the implementation of the education system.